Gambaran Intervensi Perawat dalam Asuhan Keperawatan Pasien Tuberkulosis Paru di Rumah Sakit - Muhammad Rofi'i; Bambang Edi Warsito; Agus Santoso; Sarah Ulliya (Master of Nursing, Faculty of Medicine, Universitas Diponegoro, Indonesia, 2019)
Introduction: The nurses’ role within nursing care of tuberculosis patients in hospitals is very important. Nurses problem are preparing nursing interventions in patients with pulmonary tuberculosis rarely use the standard Nursing Intervention Classification (NIC). Independent nursing interventions are not in accordance with the diagnoses established by nurses, so the impact on the implementation needed by patients is not in accordance with the problems occured. Collaborative intervention is mostly carried out by nurses compared to independent intervention. Nurses must arrange nursing interventions based on the standard of nursing diagnoses that are enforced. The objective study was to describe the interventions compiled by nurses at the hospital.Methods: Research design was qualitative research with observational approach. Sample was 100 nurse’s documentastions of pulmonary tuberculosis patient in TB MDR ward. Data analysis used language and text analysis with content analysis. Results: The results research was the highest 10 interventions written by nurses is intervention about observe general condition of patient was 83 times, collaboration with doctor’s therapy was 54 times, give comfort position was 54 times, give therapy was 47 times, check vital signs regulerly was 40 times, give oxigen was 34 times, advise to bedrest was 30 times, teach to effective cough was 25 times, Give position semi fowler was 15% times, and teach to deep breath was 15 times. Conclusion: Nurses must improve their skills and knowledge in preparing treatment plans, because the interventions that have been prepared have not been optimal for dealing with patient problems in hospitals. Interventions to improve patient knowledge and abilities in the management of the disease are important to give to patients.